The unnecessary pastor : rediscovering the call - Dawn, Marva J.; Peterson, Eugene H., 1932-2018.; Santucci, Peter (Grand Rapids, Mich. : W.B. Eerdmans ; Vancouver : Regent College Pub., 2000)
In this book, Marva Dawn and Eugene Peterson reconnect pastors with the biblical texts that will train them as countercultural servants of the gospel. Marva Dawn looks to Paul's letter to the Ephesians for instruction for churches seeking to live faithfully in today's world. In turn, Eugene Peterson explores Romans, 1 and 2 Timothy, and Titus, drawing from them the correct view of pastoral identity. --From publisher's description.
On being unnecessary / Eugene H. Peterson -- Preludes to rediscovery / Marva J. Dawn -- The call to be a living doxology / Marva J. Dawn -- Paul : finishing up in Rome / Eugene H. Peterson -- The call to triumph over the principalities and powers / Marva J. Dawn -- Timothy : taking over in Ephesus / Eugene H. Peterson -- The call to be formed and transformed by the spirit of the ascended Christ / Marva J. Dawn -- Titus : starting out in Crete / Eugene H. Peterson -- The call to build community / Marva J. Dawn.
Includes bibliographical references (pages 249-256).
Keywords: Bible. -- Criticism, interpretation, etc; Bible. -- Criticism, interpretation, etc; Clergy -- Office -- Biblical teaching